Artificial Intelligence in Smart Classrooms: An Investigative Learning Process for High School - Nasar, Ismail; Uzer, Yuspar; Aisyah; Ridayani; Purwanto, Muhammad Bambang (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study identifies instances of technological advancement where AI was used in an intelligent classroom. A learner is more likely to learn concepts via a visual medium than from a literary one, such as smart classrooms and virtual reality programs. The inability to collaborate in education utilizing AI to create a smart classroom for increasing student learning and developing achievements was one of the new technologies' shortcomings. The idea behind that is to teach the learner through visual materials that are significantly easier for them to understand and retain than text-based lessons. The smart classroom makes decisions about how measurement data and classes of elegant class features can contribute to and lead to implementing training methods for manageable improvement in the act of authentic teaching forcefully. This study's methodology focuses on providing a review of the various types of smart classroom technologies that are now available. The outcome demonstrates the considerable influence and suggests improving additional technologies utilized in smart classrooms. The Smart level demonstrates how 3D symbolism and learning techniques are used to study and understand various concepts. This article offers a thorough analysis of the smart classroom and how it can significantly advance the utilization of technology development approaches